Cutting profits and running losses: Mechanisms behind the disposition effect - Rapada, Maria Zunally (Animo Repository, 2018)
Can we balance risk attitudes simply by exposing subjects to gender stereotypes? Empirical approaches to hypothesis-testing would be inadequate in inducing relevant behavioral patterns. But with a well-designed experiment, we are able to investigate whether social and individual-level effects of gender, risk attitudes and belief in mean reversion drive traders to prematurely sell winning stocks and to cling onto losing stocks. This phenomenon, the disposition effect, has been documented across the globe for the past decades. Through trading simulations and gender priming, we found that masculine males in our experiment significantly display the disposition effect, more so than others. In addition, more men were risk averse when primed, and more women were risk seeking when amongst their male counterpart.